Evaluation of the Occupational Risk of Noise Exposure: Case Study of a Piston Compressor Manufacturer, Bangkok - Siricharoonvong, Umarat; Saejew, Nucharee; Phorthong, Rangsiya (Journal of Health Science of Thailand, 2018)
The objective of this cross-sectional study was to evaluate the risk of noise exposure among employees of a piston compressor manufacturer. The study was divided into 4 parts. The first part was to survey the primary information for classifying works sharing the same noise source. The second part was to measure the sound level at the working area in order to establish noise exposure levels. The third part was to study the secondary information that was the hearing ability test result of employees and personnel information about employees in 2009 from Human Resource Division to study the health impact. The fourth part was to analyze an average sound level measurement result at working area to sort out the hearing level and the health impact by comparing to the OSHA/ NIOSH/ACGIH recommendation and the ANSI/NIOSH, analysis the qualitative risk and sort out the risk group. The study showed that the production of motor and its cover with similar sound sources could be divided into 10 groups. From the evaluation of the risk of noise exposure, it was found that 4 groups, removing water from a work piece by blowing; punching; grinding wheel; forged crank with automated machine; grooving; and turning with a lathe; had the same risk levels resulting in mild impact on employees’ health. Other 6 groups, removing rubble from work pieces by blowing; molding small and large cover; welding ears; caulking copper pipe manually; cutting steel plate and hole punching; had low, moderate and high impact on employees’ health. It implied that the existing hearing loss protection program was not totally effective for the employees with risk level at low (5.2%), moderate (8.3 %), and high level (1.0 %). The manufacturer should provide other measures such as risk communication, training on the noise protection equipment wearing, the employees’ behavior changing on products throwing, research the noise absorbance for noise reduction from metal crashing, set pressure of the air gun to appropriate with working.